Local algebraic effect theories. (11th May 2020) - LUKŠIČ, ŽIGA; PRETNAR, MATIJA
Abstract: Algebraic effects are computational effects that can be described with a set of basic operations and equations between them. As many interesting effect handlers do not respect these equations, most approaches assume a trivial theory, sacrificing both reasoning power and safety. We present an alternative approach where the type system tracks equations that are observed in subparts of the program, yielding a sound and flexible logic, and paving a way for practical optimisations and reasoning tools.